Katy Perry [videorecording (DVD)] : part of me - Cutforth, Dan, 1967-; Lipsitz, Jane, 1965-; Perry, Katy; Kerr, Lucas; Markarian, Rachael, 1982- (Paramount, 2012)
Katy Perry is living proof that if you just be yourself, you can be anything. Get an inside look into the real Katy Perry and find out how this regular California girl with big dreams became one of the biggest stars in the world.